Synthesis, characterization, and optical and surface properties of (4-(trifluoromethylthio)phenoxy) copper(ii) phthalocyanine. (21st March 2018) - Günsel, Armağan; Bilgiçli, Ahmet T.; Pişkin, Hasan; Çaylak Delibaş, Nagihan; Yarasir, M. Nilüfer; Gündüz, Bayram
Abstract : This paper reports on the synthesis and characterization of a non-peripherally tetra-substituted copper phthalocyanine containing a 4-(trifluoromethylthio)phenoxy group. Abstract : This paper reports on the synthesis and characterization of a non-peripherally tetra-substituted copper phthalocyanine containing a 4-(trifluoromethylthio)phenoxy group. The synthesized compounds have been characterized using elemental analysis, FTIR, 1 H NMR, 13 C NMR, MALDI-TOF, SEM and UV-vis spectral data. The crystal structure of 3-(4-(trifluoromethylthio)phenoxy)phthalonitrile (1 ) was confirmed by single-crystal X-ray diffraction. The crystallographic information file (cif) was uploaded to the data center with CCDC ;1538643 . We investigated the UV-vis spectra, band edge, band gap, refractive indices, dispersion, sensing, conductance and dielectric properties. The surface morphological properties of the Cu(ii )Pc (2 ) film were investigated under different conditions.